Quality loss assessment and an optimization approach for scheduling fresh fruit exporting operations - Damrongpol K. (2017)
Mechanical damage to fresh fruits and vegetable during transportation is significant in logistics cost for export companies. Many global companies have tried to control the product quality throughout the food supply chain. However, the cost of quality loss due to the mechanical injuries during transportation is difficult to identify accurately and incorporate into logistics cost model. In this paper, we propose the methodology to formulate the mathematical model to maximize revenue that considered not only common logistic cost but also the physical injuries cost due to shock and vibration during transportation. The resulting model can be applied in an illustrative case study for the other FFV, and can be used to design and operate food distribution system both in term of export plan and marketing plan in each day during fruit season period.